iLearn: Electronic-English Teaching Platform Based on Artificial Intelligence (AI) For the College Students - Herdina, Griselda Gian Heris; Aini, Nurul (Proceeding International Conference on Religion, Science and Education, 2024)
The use of technology in teaching English in college must be continually updated due to the high tense of students and teachers in applying it. Moreover, the industrial revolution 4.0 era which was marked by automation and the exchange of data on where most people used the Internet to site, search, analyze data and information, and access cloud services. In addition, it is in line with the 5.0 society era which is intended to bring human centered on the technological and economic sides that use virtual and reality systems to solve various problems. Educational technology has revolutionized teaching and learning into an innovative use of artificial intelligence (AI) in the university. The one of innovation is based on AI is iLearn. It designed to find out the needs of the students and to know the mastery of the students’ material based on the curriculum through programs that provide ease of teaching activities in college. This reserach discusses the innovation based on integration between learning English and the sophistication of AI will have advantages over previous teaching techniques. The article limits to discuss about how this AI system operates to make learning more conducive. For the result, iLearn strives for a rewarding experience for students in full-featured English learning in its latest version and will suit of English learning curriculum.